Juan Pablo Forner in the “Dramatic poetry”: The lost works - Cañas Murillo, Jesús (2023)
This article rescues from oblivion the fragments and news that have been preserved from the lost dramatic works of Juan Pablo Forner: Scene I of Act III of the tragedy Las Vestales, and the data on the composition and plot of La Cautiva Española. Included, in a critical edition with textual notes, are the two texts that the native of Merida himself managed to preserve from these two of his creations, the fragment of Las Vestales included in the «Ilustraciones» to the second of his Discursos filosóficos sobre el hombre, and his Carta de don Juan Pablo Forner [...] a Don Ignacio López de Ayala [...] sobre haberle desaprobado su drama intitulado La Cautiva española. With this work we wanted to contribute to improve the knowledge we have today of the written production bequeathed by Forner to posterity, and to disseminate it among today’s interested readers.